DAMPAK KEBIJAKAN EKONOMI TERHADAP INDUSTRI KOMODITI KELAPA SAWIT DAN KARET INDONESIA - Liston Siringo Ringo (Jurnal Bisnis Tani, 2015)
Palm oil and natural rubber are export commodities which have important role in generating Indonesian foreign exchange. Export share of both these commodities is about 62 percent from the total of plantation sub-sector export. It is assumed that economic policy has significant impact on the development of Indonesian palm oil and natural rubber industries. The general aim of the research is to analyze the impact of the various economic policies on oil palm and rubber industries. This study was using a system approached by formulating an econometric model of palm oil and rubber industries. The model specification was dynamic-simultaneous and consisted of 44 structural and 18 identities equations. The model estimation was conducted by using Two Stage Least Square (2SLS) method. The results of the research showed that: (1) decreasing interest rates gave a positif impact on the mature area, (2) increasing in farm input prices such as wage rate and fertilizer prices gave a negatif impact on the mature area, (3) exchange rate depreciation gave a positif impact on increasing export and (4) decreasing palm oil export tax gave a positif impact on export prices, whereas it will be an incentive for palm oil producers to expand the plantation area.